Kajian Pendahuluan E-modul Berbasis Etnosains Danau Ranau Untuk Meningkatkan Keterampilan Literasi Siswa Pada Topik Energi Terbarukan - Komarudin Komarudin; Hamdi Akhsan; Ketang Wiyono (Postgraduate, University of Mataram, 2025)
This study aims to identify the needs in the physics learning process from the perspectives of students and teachers. A survey method was used by distributing questionnaires to 184 students and 40 physics teachers in South Sumatra, selected through purposive sampling. The results show that students better understand physics when it is related to natural phenomena and everyday life, such as renewable energy. However, they face challenges with formulas, scientific terms, and connecting concepts to real-life contexts. Both students and teachers agree that integrating ethnoscience into physics learning can effectively enhance scientific literacy. All participants stated the need for learning resources that incorporate ethnoscience from Lake Ranau in Ogan Komering Ulu, South Sumatra. Based on these findings, an e-module was developed featuring concise explanations, visual elements, videos, interactive quizzes, and practical experiment activities. The results indicate the importance of developing an ethnoscience-based e-module to improve students' literacy in the topic of renewable energy.